THE CLINICAL AND METABOLIC EFFECTS OF CALCITRIOL IN THE TREATMENT OF POSTMENOPAUSAL OSTEOPOROSIS - Güneş Yavuzer; Serpil Savaş; Peyman Yalçın; Gülay Dinçer; Atilla Elhan (Archives of Rheumatology, 2000)
Osteoporosis is the most common metabolic disease of bone whose management is controversial. To evaluate the efficacy and safety of calcitriol (1,25-dihydroxyvitamin DJ in postmenopausal osteoporosis, this prospective, randomized, one-year clinical trial was planned. Seventy patients aged between 45-69 years were randomly assigned to receive either calcitriol (0.25gr twice daily) or supplemental calcium (1gr/day) for one year. Lumbar spine and femoral neck bone mineral density (BMD) values, pain intensity and disability measure scores and bone turnover markers Jerum osteocalcin and urinary hydoxyproline levels) were used as outcome parameters of treatment. The groups were similar with regard to age, body mass index, years since menopause, baseline bone mineral measurements, pain intensity and disability measure scores initially. In calcitriol group, lumbar spine BMD values, pain intensity and urinary hydroxyproline levels were significantly improved at the end of the trial whereas no change was observed in femoral neck BMD values, disability measures and serum osteocalcin levels. No significant changes of outcome parameters were found in calcium group. The compliance to treatment protocols was high and no clinical or laboratory side effect of drugs was observed. As a conclusion calcitriol treatment was found to be effective and safe in the treatment of postmenopausal osteoporosis.